Increase of efficiency isopropylbenzene manufacturing with use of integrated mathematical models; Petroleum and Coal; Vol. 58, iss. 2 - Chudinova A. A. Alyona Anatoljevna; Buchatskaya N. I. Nadezhda; Podgorniy V. V. Vladimir; Gavrikov А. А. Aleksey Alekseevich; Ivashkina E. N. Elena Nikolaevna; Dolganova I. O. Irena Olegovna (2016, 2016)
Title screen